Mixed Monotone Iterative Technique for Abstract Impulsive Evolution Equations in Banach Spaces. (14th September 2010) - Yang, He
Abstract : By constructing a mixed monotone iterative technique under a new concept of upper and lower solutions, some existence theorems of mildω -periodic (L -quasi) solutions for abstract impulsive evolution equations are obtained in ordered Banach spaces. These results partially generalize and extend the relevant results in ordinary differential equations and partial differential equations.